Microcirculatory and Hemostatic Changes in Patients after Endoprosthetic Hip Joint Replacement - P. V. Gromov; K. G. Shapovalov (Общая реаниматология, 2011)
Objective: to estimate the values of microcirculation, hemostasis, and fibrinolysis in patients after hip joint replacement. Subjects and methods. Thirty-two patients were examined after total endoprosthetic hip joint replacement (TEHJR). Microcirculation was explored by laser Doppler flowmetry (LDF). The level of ADAMTS-13 and its inhibitor and the concentrations of tissue factor pathway inhibitor (TFPI), tissue plasminogen activator (t-PA), and tissue plasminogen activator inhibitor-1 (PAI-1) were measured in the patients’ plasma by enzyme immunoassay. Results. Analysis of LDF measurements of the operated limb showed a 1.3-fold reduction in the value of microcirculation as compared with the intact limb in the patients in the early postoperative period after TEHJR. There were 1.3- and 1.4-fold increases in neurogenic and myogenic tones, respectively. The shunting ratio was 15% higher in the operated versus intact limb. The content of ADAMTS-13 was increased by 1.4-fold in the blood of the operated limp. As compared with the control group, the blood level of TFPI in the operated and intact limbs was elevated by 1.8 and 1.6 times, respectively. As compared with the controls, the patients after hip joint replacement displayed 1.9- and 1.6-fold decreases in the blood concentration of t-PA and PAI-1, respectively. Conclusion. In the patients after hip joint replacement, the value of microcirculation was lower, neurogenic and myogenic tones were higher, as well as there were increases in the levels of ADAMTS-13 and TFPI in the blood flowing from the operated limb as compared with the intact one. The plasma content of t-PA and PAI-1 became lower in the post-TEHJR patients than that in the control group. Key words: endoprosthetic hip joint replacement, microcirculation, hemostasis.